GE_GERICHTE C/14155/2014 vom 8. Mai 2015 - GE Cour de justice (2015)
MAINLEVÉE DÉFINITIVE; TITRE EXÉCUTOIRE; ASSURANCE SOCIALE; DÉCISION; PRIME D'ASSURANCE | LP.80.1; LAA.1a.1; LAA.4; OLAA.117.2; LPGA.54.2